The fabrication of ClNCNTs/Fe3O4 nanoparticles for the removal of Pb2+ ions in aqueous solution - Sebake, Morongwa Sowela Mary-Jane (Vaal University of Technology, 2021)
Removal of wastewater pollutants is urgent as they are continuously defiling the limited freshwater resources, affecting the ecosystem, aquatic and terrestrial life. Carbon nanotubes-based adsorbent materials are effective for removal of wastewater pollutants owing to their large specific surface area. Surface modification of carbon nanotubes (CNTs) can mediate specific pollutant adsorption and increase CNTs colloidal stability and chemical reactivity. Heavy metal pollution of wastewater is one of the major threats, as this metals can be toxic to humans when present at certain concentrations in drinking water. This study report the synthesis of chlorine functionalized and nitrogen doped carbon nanotubes (ClNCNTs) loaded with iron oxide nanoparticles and their use as adsorbents for Pb2+ ions in aqueous solutions. Carbon nanomaterials that are functionalized with chlorine and doped with nitrogen were successfully synthesized. This was done through pyrolysis of a mixture of dichlorobenzene and acetonitrile (in a 1:1 volume ratio) over 10% Fe-Co/CaCO3 bi-metallic catalyst via chemical vapour deposition (CVD) method. Addition of chlorine and nitrogen to the CNTs was to enable defect and disorder creation on the surface of the nanotubes which is envisaged to create nucleation sites on the their surface for better adhesion of the iron oxide nanoparticles. Different loadings of magnetite (Fe3O4) nanoparticles on the surface of the ClNCNTs was achieved using a co-precipitation method. The synthesized materials were charaterized by Raman spectroscopy, Transmission electron microscopy (TEM), Powder X-ray diffraction (PXRD) spectroscopy, Thermal gravimetric analysis (TGA), Brunauer Emmett and Teller (BET) and X-ray photoelectron spectroscopy (XPS). Highly defected CNTs, some with hollow and others with bamboo-compartments due to nitrogen inclusion were obtained. The effect of metal salt concentration in wt.% (10, 20, 30 and 53 wt.%) was investigated. The increase in wt.% loading has resulted in an increase in surface area, and a decrease in thermal stability as a result of defected Fe3O4/ClNCNTs. In addition, agglomeration was observed at 30 and 53 wt.% loading, due to large amount of iron present. The identity of the Fe3O4 nanoparticles was confirmed by PXRD and XPS with two iron peaks deconvoluted at 725.6 eV and 721 eV respectively. The percentage loading of the Fe3O4 nanoparticles at the surface of the ClNCNTs was affirmed by TGA analysis, where the residual mass obtained from TGA were closely related to the mass percentages added. Different nitrogen environments namely, the quatenary, pyridinic, pyrollic and nitrogen oxides were also observed, whilst chlorine could not be deconvoluted because it was present in very limited amount probably it was masked by the iron oxide nanoparticle. Thus, a 20 wt.% Fe3O4/ClNCNTs was chosen as an optimum, due to uniform distribution of spherical nanopaticles observed along the radial length of ClNCNTs that had an average size of 10 ± 4.5 nm. The synthesized ClNCNTs and a nanocomposite made from a 20 wt.% Fe3O4/ClNCNTs were applied in the removal of Pb2+ ions from aqueous solution. The results obtained showed that a nanocomposite made from a 20 wt.% Fe3O4/ClNCNTs had a better adsorption capacity of 17.0 mg/g as compared with 14.8 mg/g for ClNCNTs.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Ions in aqueous solution; Removal of wastewater pollutants; Heavy metal pollution; Nanoparticles; Pollutant adsorption; Dissertations, Academic -- South Africa.; Water -- Pollution.; Nanostructured materials.; Water -- Purification -- Biological treatment.; Water chemistry.